PERANAN LEASING SEBAGAI LEMBAGA PEMBIAYAAN PERUSAHAAN - Agnes Maria Janni Widyawati (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2019)
With the increase in economic development increasingly diverse sources of financing are no longer limited to bank credit loans or sources of money and capital markets. In Indonesian financing law, there are various forms of financing institutions, one of which is a leasing or leasing institution according to article 1 of the Joint Decree of the Minister of Finance, Minister of Industry and Minister of Trade No. 122 / MK / IV / 2/1974, No. 32 / M / SK / 2/1974, No. 30 / Kpb / I / 1974 concerning Leasing Business Licensing, what is meant by leasing is: "Every company financing activities in the form of providing capital goods for use by a company for a certain period of time, based on periodic payments accompanied by voting rights ( option) for the company to buy the relevant capital goods or extend the lease period based on the agreed residual value ". From the formulation above, it turns out to focus more on the economic aspects, so that looking at leasing as an act, economical, which is an activity corporate financing in the form of providing capital goods.